The Student Leadership Challenge : Five Practices for Becoming an Exemplary Leader. / James M Kouzes; Barry Z Posner - Kouzes, James M
In this updated and expanded second edition of The Student Leadership Challenge, James Kouzes and Barry Posner apply their extensive research and expertise to demonstrate that anyone can be a leader, regardless of age or experience. They challenge high school and undergraduate college students to examine their leadership actions and aspirations. Your students will learn from first-hand leadership stories from young leaders like themselves around the world, helping them to deeply understand and explore The Five Practices of Exemplary Leadership®: Model the WayInspi